2014
DOI: 10.1111/bph.12528
|View full text |Cite
|
Sign up to set email alerts
|

The ryanodine receptor agonist 4‐chloro‐3‐ethylphenol blocks ORAI store‐operated channels

Abstract: BACKGROUNDDepletion of the Ca 2+ store by ryanodine receptor (RyR) agonists induces store-operated Ca 2+ entry (SOCE). 4-Chloro-3-ethylphenol (4-CEP) and 4-chloro-m-cresol (4-CmC) are RyR agonists commonly used as research tools and diagnostic reagents for malignant hyperthermia. Here, we investigated the effects of 4-CEP and its analogues on SOCE. EXPERIMENTAL APPROACHSOCE and ORAI1-3 currents were recorded by Ca 2+ imaging and whole-cell patch recordings in rat L6 myoblasts and in HEK293 cells overexpressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…We found that 2-APB had no effect on FSE-mediated GLUT4 translocation under 2 mM extracellular Ca 2+ , but it evidently inhibited FSE-triggered Ca 2+ release ( Figure 6 A). The ryanodine receptor (RyR), another channel that releases Ca 2+ in the sarcoplasmic reticulum (SR)/endoplasmic reticulum (ER) [ 40 ], has attracted much attention due to its manipulation of intracellular Ca 2+ output. Inhibition of RyR with 30 μM ryanodine had no effect on either GLUT4 translocation or intracellular Ca 2+ increase mediated by FSE ( Figure 6 B).…”
Section: Resultsmentioning
confidence: 99%
“…We found that 2-APB had no effect on FSE-mediated GLUT4 translocation under 2 mM extracellular Ca 2+ , but it evidently inhibited FSE-triggered Ca 2+ release ( Figure 6 A). The ryanodine receptor (RyR), another channel that releases Ca 2+ in the sarcoplasmic reticulum (SR)/endoplasmic reticulum (ER) [ 40 ], has attracted much attention due to its manipulation of intracellular Ca 2+ output. Inhibition of RyR with 30 μM ryanodine had no effect on either GLUT4 translocation or intracellular Ca 2+ increase mediated by FSE ( Figure 6 B).…”
Section: Resultsmentioning
confidence: 99%
“…43 . T-REx HEK293 cells (Invitrogen) were routinely cultured and transfected with the above two plasmids to obtain stable expression of Orai1 and STIM1 in this cell line.…”
Section: Methodsmentioning
confidence: 99%
“…To assess intracellular Ca 2 + release, we studied the responses to chlorophenol derivatives and ATP. Ad.CAGMiC -infected human fibroblasts at day 14 or normal human fibroblasts were examined in the absence and presence of the ryanodine receptor stimulants 4-CEP or 4-CmC [16] . Extracellular ATP stimulates P2Y receptors to activate phospholipase C, thereby promoting the production of IP3 and the consequent stimulation of the IP3 receptor [17] .…”
Section: Resultsmentioning
confidence: 99%